2021
DOI: 10.1093/trstmh/trab137
|View full text |Cite|
|
Sign up to set email alerts
|

The management of moderate acute malnutrition in children aged 6-59 months in low- and middle-income countries: a systematic review and meta-analysis

Abstract: Background Malnutrition is a leading cause of morbidity and mortality in children aged <5 y, especially in low- and middle-income countries (LMICs). Unlike severe acute malnutrition, moderate acute malnutrition (MAM) affects greater numbers globally, and guidelines lack a robust evidence base. This systematic review and meta-analysis assessed the evidence for lipid-based nutrient supplements (LNSs), fortified blended flours (FBFs) and nutrition counselling, in the treatment of MAM. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Furthermore, the authors highlighted the potential to enhance the effectiveness by focusing on improving the quality and adherence to counseling interventions. A more recent systematic review by Gluning et al (2021) also found that children had a greater likelihood of recovery if they received a specially formulated food than if they did not [33].…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…Furthermore, the authors highlighted the potential to enhance the effectiveness by focusing on improving the quality and adherence to counseling interventions. A more recent systematic review by Gluning et al (2021) also found that children had a greater likelihood of recovery if they received a specially formulated food than if they did not [33].…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…Several studies have evaluated the effects of the supplement matrix or different protein sources on recovery from MAM and growth. Reviews and meta-analyses have often found superior recovery among children treated with LNS vs FBF [4][5][6][7]. Some reviews found higher gain in weight, weight-for-height z-score (WHZ), or MUAC [5][6][7][8], but not height [8] when children with MAM were treated with LNS compared to CSB.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable discrepancies exist between the treatment protocols in different countries (14)(15)(16)(17)(18). MAM protocols may implement readyto-use supplementary food (RUSF), fortified flours, nutrition education or counselling to improve child's nutritional status (19,20). Differences also exist in the cut-off points of the anthropometric indicators mid-upper arm circumference (MUAC) and/or weight-forheight Z-score (WHZ) that determine admission and cure.…”
Section: Introductionmentioning
confidence: 99%